2000
DOI: 10.1111/j.1365-2141.2000.02373.x
|View full text |Cite
|
Sign up to set email alerts
|

A new polymorphism in the human factor VIII gene: implications for linkage analysis in haemophilia A and for the evolution of int22h sequences

Abstract: Summary.A new polymorphism in the human factor VIII gene has been localized and characterized. It is a biallelic, single nucleotide polymorphism located in intron 22 of the gene, within the 9´5 kb int22h-1 segment. The allelic forms are G (frequency 0´65) and A (frequency 0´35), giving a predicted rate of heterozygosity of 0´46. The polymorphism occurs within a CG dinucleotide and affects an MspI site (CCGG). Int22h-1 is duplicated twice extragenically at Xq28; both extragenic copies (int22h-2 and -3) are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…In addition, the MspI polymorphism of int22h-1, which is 737 bp away from the XbaI polymorphism site, had a heterozygosity rate of 49.5%, and allelic frequencies were 0.61 and 0.39, respectively, for the (+) and (-) alleles (allele +/-= 0.61/0.39 ± 0.0335, 95%CI) in this study. These results are similar to those of Bowen et al (2000), where the heterozygosity rate was 0.46, and allelic frequencies were 0.65 and 0.35, respectively, for the (+) and (-) alleles in 85 male hemophilia A patients in South Wales. This information suggested that a slightly higher informative rate was obtained in the Korean population.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In addition, the MspI polymorphism of int22h-1, which is 737 bp away from the XbaI polymorphism site, had a heterozygosity rate of 49.5%, and allelic frequencies were 0.61 and 0.39, respectively, for the (+) and (-) alleles (allele +/-= 0.61/0.39 ± 0.0335, 95%CI) in this study. These results are similar to those of Bowen et al (2000), where the heterozygosity rate was 0.46, and allelic frequencies were 0.65 and 0.35, respectively, for the (+) and (-) alleles in 85 male hemophilia A patients in South Wales. This information suggested that a slightly higher informative rate was obtained in the Korean population.…”
Section: Discussionsupporting
confidence: 77%
“…The XbaI and MspI polymorphisms are located within a 9.5-kb stretch of the int22h-1 sequence. The extragenic homologous sequences, int22h2-2 and int22h-3, also have polymorphic sites for XbaI and MspI (Chan et al, 1989;Naylor et al, 1995;Bowen et al, 2000). Thus, detection of XbaI/int22h-1 and MspI/int22h-1 polymorphisms at the three polymorphic sites of int22h would require efficient amplification of those specific sequences (De Brasi et al, 1999;El-Maarri et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A dimorphism within intron 22, MspA1I, has been described which is in close proximity to XbaI dimorphism but is not in complete linkage disequilibrium and may be useful in some family studies [7].…”
Section: Editorial Husainmentioning
confidence: 99%